Efficacy of lyophilised bacteria-rich faecal sediment and supernatant with reduced bacterial count for treating patients with Clostridioides difficile Infection – A novel method for capsule faecal microbiota transfer - Varga, Adorján; Makszin, Lilla; Bufa, Anita; Sipos, Dávid; Kása, Péter; Pál, Szilárd; Rosenstiel, Philip; Sommer, Felix; Kocsis, Béla; Péterfi, Zoltán (Frontiers in Cellular and Infection Microbiology, 2023)
BACKGROUND & AIMS: Faecal microbiota transfer (FMT) has managed to earn its place in the Clostridioides difficile infection (CDI) guidelines by having comparable efficacy and recurrence rate of fidaxomicin. After more than 100 successful FMT administration through nasogastric tube, we started using hard gelatine capsules filled with lyophilised faecal sediment and supernatant. Our main question was whether uncoated capsules (containing faecal sediment or supernatant) are comparable to the widely used nasogastric tubes in CDI. We also investigated the effect of storage and time on the survival rate of bacteria in the samples. METHODS: We compared the efficacy of our capsules to other treatment options of CDI at the Department of Infectology at the University of Pécs (Hungary). For our study, stool was collected from a single donor. We treated 10 patients with relapsing CDI, 5 of them received supernatant, 5 received sediment. Donor samples were stored on 4 different temperatures and tested to determine the survival rates of bacteria. As pilot projects, we also assessed the changes of bacterial taxa, protein- and lipid compositions. Moreover, we selected 4 patients to compare their samples prior and after FMT by using microbiome (16S amplicon sequencing), protein, and lipid analyses. RESULTS: 4 out of the 5 patients who received supernatant became symptomless within 2 days after FMT. In the sediment group 3 out of 5 patients were cured from CDI. Comparing the supernatant to the sediment, we found significantly lower number of colony-forming units in the supernatant. We found that -80°C is the most suitable temperature to store the samples. The stool lipid profiles of recipients showed a more diverse composition after FMT, and changes in the stool protein profiles were observed as well. In the microbiome analysis, we observed an increase in the alpha diversity after FMT. CONCLUSIONS: Our study of 10 patients showed good efficacy of lyophilised faecal supernatant using capsules. The single donor approach proved to be effective in our investigation. A significantly lower CFU number was sufficient for the effect, the separation can be achieved by widely available instruments. For storage temperature, -20°C was sufficient in our clinical practice.